Harmoni Ekowisata Mangrove: Memahami Tantangan Dan Dinamika Pengelolaan Berkelanjutan Di Kawasan Lantebung, Kota Makassar - Anwar, Amirul Ahsan; Hasyim, Muhammad; Nasruddin, Nasruddin; Sirih, Syahid (JURNAL DESTINASI PARIWISATA, 2024)
This research discusses efforts to develop the sustainable tourism sector in Indonesia, focusing on mangrove ecotourism. With Indonesia having the world's largest mangrove forest, harnessing the potential of ecotourism is seen as a means to preserve natural and cultural diversity. Case studies in the Mangrove Ecotourism Area of Tahura Ngurah Rai, Bali, and Makassar City, particularly in Lantebung, demonstrate the successful development of mangrove ecotourism with positive impacts on social, economic, and ecological aspects. However, challenges such as infrastructure, regulations, and public awareness remain obstacles. Research in Lantebung Village utilizes a dynamic systems approach, identifying issues, collecting data, and developing models to contribute to a holistic understanding of mangrove ecotourism management dynamics. The study provides a descriptive overview of the mangrove ecosystem in Lantebung, with the hope that further information and quantitative data will support a deeper understanding in the future. The findings highlight the importance of supporting ecotourism with its principles, creating a conducive environment, and addressing issues such as community control, social efficiency, biopiracy risks, and balancing the needs of investors with the participation of local communities. The emphasis on a dynamic systems approach underscores the need for comprehensive planning and sustainable practices in mangrove ecotourism development in Indonesia. Keywords: sustainable tourism, ecotourism, dynamic system, mangrove ecotourism, and lantebung